“Self-Sufficient” Column in the Art of the Northern Renaissance: Negative and Positive Connotations of the Image - Popova, Vera L. (Actual Problems of Theory and History of Art, 2021)
The article examines the giving of a special meaning to a separate column as the issue of iconology of the architectural order. It focuses on the monuments of the Netherlands and Germany of the 16th — first half of the 17th centuries: engravings, elements of facade architectural decor and church interior, etc. E. Forssman’s dissertation “Säule und ornament. Studien zum Problem des Manierismus in der nordischen Säulenbüchern und Vorlagenblättern des 16. und 17. Jahrhunderts”, published in Stockholm in 1956, has been taken as the basis for the study. For the first time the scientist drew attention to the specific traits of the reception of architectural order by the masters of the Northern Renaissance, for whom the “meaning-endowing” of the support prevailed over its tectonic functions, analyzing at the same time some cases of using the image of the column within the framework of religious themes.The study considers the cases of “self-sufficiency” of the column noted by the Swedish researcher in more detail, supplements them with examples from the field of engraving and architectural practice of the period under consideration, identifies other precedents of such “meaning-endowing” of the column (including precedents of positive connotations), structures and systematizes the available information, including the appearance of these subjects in Russian art of the 18th century, when the latter begins to show a noticeable interest in Western European models.This study is based on the research, supported by the Program of Fundamental Research of the Russian Academy of Architecture and Construction Sciences and of the Ministry of Construction, Housing and Utilities of the Russian Federation — 2021.
Keywords: order; iconology; column; Northern Renaissance; 16th –17th centuries; Germany; Netherlands; Eric Forssman; Piscator’s Bible